Climate and land-use change as driving forces in lowland semi-natural vegetation dynamics - Lundberg, Anders (ERDKUNDE, 2011)
In many parts of Europe, extensive changes in vegetation have taken place during recent decades. In Norway, forest expansion is a major trend, with an increase in volume of 20.3% during the period 1994–2008. The annual increase has more than doubled since 1967. This study was carried out to gain more insight into the complexity of vegetation dynamics and alterations in a lowland area on the coast of W Norway, and to identify the driving forces behind these changes. Field surveys were carried out with aerial photo interpretation and vegetation mapping. Spatial analysis was carried out using GIS. Historical sources were identified, interpreted, and used to generate information on land-use during recent centuries. Supplementary methods consisted of soil profile analysis and dendrochronology. Climate data were used to analyse climatic trends in the past 90 years since 1923. Forest expansion was a major trend during 1956–1994. In 1956, 49.5% of the area was covered by forest, and by 1994 the coverage had increased with 53.4%. Forestation continued during 1994–2003 and 2003–2007, but at rates far lower than in the previous period (4.0 and 3.8% increases, compared to 53.4%). Forest expansion was most extensive during 1956–1994, a period with no clear trend in mean July temperatures. A distinct increase in mean July temperatures occurred during the period 1994–2003 and again in 2003–2007, when the rate of forestation was far lower than in previous decades. This is an indication that a factor other than climate change is the most important driving force for vegetation change, forest expansion in particular. Forestation did not start simultaneously throughout all parts of the study area, but at different times on different landholdings. Forestation initially started on plots where livestock grazing first came to an end (in the 1930s), and lastly on plots where grazing came to an end three decades later, in the 1960s. The different starting times of forestation is reflected in the present age structure of the forest stands on the eight landholdings studied. The conclusion is drawn that changes in land-use are the major driving force behind the distinct process of forestation that occurred during the 20th century.